2020
DOI: 10.1016/j.ebiom.2020.103131
|View full text |Cite
|
Sign up to set email alerts
|

High throughput profiling of undifferentiated pleomorphic sarcomas identifies two main subgroups with distinct immune profile, clinical outcome and sensitivity to targeted therapies

Abstract: Background Undifferentiated pleomorphic sarcoma (UPS) is the most frequent, aggressive and less-characterized sarcoma subtype. This study aims to assess UPS molecular characteristics and identify specific therapeutic targets. Methods High-throughput technologies encompassing immunohistochemistry, RNA-sequencing, whole exome-sequencing, mass spectrometry, as well as radiomics were used to characterize three independent cohorts of 110, 25 and 41 UPS selected after histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…In UPS, our data finds that this subgroup is enriched in gene sets associated with leukocyte activation. This result is consistent with a very recent transcriptomic study which showed that UPS can been classified into two distinct molecular subgroups, one of which is characterised by genes involved in inflammatory response and immune cell signatures [ 9 ]. The enrichment of an immune cell proteomic signature in UPS, where immune checkpoint inhibitors have showed some clinical activity [ 26 , 27 ], suggests that future inclusion of proteomic profiling in cancer immunotherapy trials may lead to new predictive biomarkers that complement currently available approaches [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In UPS, our data finds that this subgroup is enriched in gene sets associated with leukocyte activation. This result is consistent with a very recent transcriptomic study which showed that UPS can been classified into two distinct molecular subgroups, one of which is characterised by genes involved in inflammatory response and immune cell signatures [ 9 ]. The enrichment of an immune cell proteomic signature in UPS, where immune checkpoint inhibitors have showed some clinical activity [ 26 , 27 ], suggests that future inclusion of proteomic profiling in cancer immunotherapy trials may lead to new predictive biomarkers that complement currently available approaches [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study utilised the reverse phase protein array (RPPA) platform which is limited to the analysis of 192 proteins/phosphoproteins. Other studies that utilise mass spectrometry (MS) have largely been limited to 1–2 subtypes including recent proteomic analyses of gastrointestinal stromal tumours (GIST) and undifferentiated pleomorphic sarcomas (UPS) which identified distinct clinical and molecular subgroups [ 6 , 8 , 9 ]. To date few MS-based analysis has been conducted across multiple histological subtypes in STS.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Toulmonde et al recently used a multi-omics platform to characterize UPS and identified a subgroup of UPS characterized by low expression of markers of immune activation. This subgroup showed an enrichment in genes involved in development and stemness including in particular FGFR2 , which they propose to potentially represent a therapeutic target [ 49 ]. Similarly, FGFR1 and FGFR2 transcripts are enriched in subtype I of LMS, a transcriptionally defined molecular subtype characterized by the overexpression of genes involved in muscle contraction, muscle system processes, and cytoskeleton organization [ 50 ].…”
Section: The Roles Of Fgf/fgfr Pathway In Gist and Stsmentioning
confidence: 99%
“…In FGFR2-overexpressing myxoid liposarcoma cell lines, the FGFR TKIs PD173074, dovitinib and infigratinib, reduced cell proliferation and migration, and this effect was further increased by their combination with the standard chemotherapeutic agent trabectedin [ 41 ]. Recently, the FGFR TKIs erdafitinib, infigratinib, and AZD4547 have been shown to decrease in vitro viability, FGFR2 phosphorylation, and downstream signaling, and induced G0–G1 arrest in cells derived from immune-low UPS, which are characterized by the overexpression of FGFR2 [ 49 ]. Finally, pharmacological FGFR inhibition significantly impaired the growth of patient-derived xenografts from immune-low UPS, but had no effect on those from immune-high UPS [ 49 ].…”
Section: Fgfr Inhibition In the Therapy Of Gist And Stsmentioning
confidence: 99%
See 1 more Smart Citation